2018
DOI: 10.21037/atm.2018.10.57
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation disorders

Abstract: Fatty acid oxidation disorders (FAODs) are inborn errors of metabolism due to disruption of either mitochondrial β-oxidation or the fatty acid transport using the carnitine transport pathway. The presentation of a FAOD will depend upon the specific disorder, but common elements may be seen, and ultimately require a similar treatment. Initial presentations of the FAODs in the neonatal period with severe symptoms include cardiomyopathy, while during infancy and childhood liver dysfunction and hypoketotic hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 61 publications
2
151
0
15
Order By: Relevance
“…Prevalence [16] Acylcarnitine elevations [17] CPT-IAD CPT1A 1:750,000 to 1:2,000,000 C0, C0/(C16 + C18) ratio CACTD SLC25A20 C16, C16:1, C18 C0 free carnitine, CACTD carnitine-acylcarnitine translocase deficiency, CPT-IAD/CPT-IID carnitine palmitoyltransferase I/II deficiency, FAOD fatty acid oxidation disorder, LC-FAOD long-chain fatty acid oxidation disorders, LCHADD long-chain L-3 hydroxyacyl-CoA dehydrogenase deficiency, MCADD medium-chain acyl-CoA dehydrogenase deficiency, TFPD tri-functional protein deficiency, VLCADD very-long-chain acyl-CoA dehydrogenase deficiency before they were two years old, with approximately one-third first presenting as neonates [23]. A large proportion (46%) in this series presented with hypoketotic hypoglycemia; other symptoms reported in infants were coma triggered by fasting or catabolism, Reye Syndrome-like episodes, cardiomyopathy, and symptoms of acute myolysis [23].…”
Section: Genementioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence [16] Acylcarnitine elevations [17] CPT-IAD CPT1A 1:750,000 to 1:2,000,000 C0, C0/(C16 + C18) ratio CACTD SLC25A20 C16, C16:1, C18 C0 free carnitine, CACTD carnitine-acylcarnitine translocase deficiency, CPT-IAD/CPT-IID carnitine palmitoyltransferase I/II deficiency, FAOD fatty acid oxidation disorder, LC-FAOD long-chain fatty acid oxidation disorders, LCHADD long-chain L-3 hydroxyacyl-CoA dehydrogenase deficiency, MCADD medium-chain acyl-CoA dehydrogenase deficiency, TFPD tri-functional protein deficiency, VLCADD very-long-chain acyl-CoA dehydrogenase deficiency before they were two years old, with approximately one-third first presenting as neonates [23]. A large proportion (46%) in this series presented with hypoketotic hypoglycemia; other symptoms reported in infants were coma triggered by fasting or catabolism, Reye Syndrome-like episodes, cardiomyopathy, and symptoms of acute myolysis [23].…”
Section: Genementioning
confidence: 99%
“…The onset of peripheral neuropathy can vary based on underlying FAOD; however, it persists as a progressive presentation of the disease. As the neuropathy progresses, it can require more frequent clinical monitoring, although its treatment can be difficult [17]. Moreover, since this manifestation is irreversible, it poses a lifelong impact on patient QoL [46].…”
Section: Qol Impactmentioning
confidence: 99%
“…FA oxidation disorders (FAODs) include defects of metabolism caused by abnormalities in either mitochondrial β-oxidation or the import of FA in the mitochondrial matrix via the carnitine shuttle [199]. The former are determined by recessive mutations in genes encoding for the very long-chain acyl-CoA dehydrogenase (VLCAD), the long chain 3-hydroxy-acyl-CoA dehydrogenase (LCHAD) and the trifunctional mitochondrial protein (TFP).…”
Section: Fatty Acid Oxidation Disordersmentioning
confidence: 99%
“…In this situation free fatty acid oxidation plays an important role for energy homeostasis. Disorders of free fatty acid metabolism are associated with occurrence of hypoglycemia [15]. Studies from analbuminemic rats have shown improved insulin sensitivity, increased insulin secretion, faster depletion of liver glycogen stores during fasting, free fatty acid deficiency with reduced rates of hepatic lipogenesis, triglyceride secretion, and limited lipoprotein lipase activity [4,5].…”
Section: Discussionmentioning
confidence: 99%